Kebutuhan Luasan Areal Hutan Kota sebagai Rosot (Sink) Gas CO2 untuk Mengantisipasi Penurunan Luasan Ruang Terbuka Hijau di Kota Bogor - Dachlan N. Endes (Forum Geografi, 2011)
The purpose of this study was to determine the need of the urban forest area as sink (sequestration) of CO2 gas from fuel oil and gas in Bogor City. Analysis of dynamic system is used to determine the need. Powersim software with the license number PSSL-N999998-5NC2Y was used in this research. Satellite imagery in 2003, 2005 and 2007 were used to analyze the extent of green space and built space as well as percentage changes. This study revealed that the urban forest area required as well as the number of seedlings are varies according to time and the sink rate. Therefore, the selection of tree species based on the sink rate should really be considered. By using the very high-sink rate trees, the area needed for this purpose will be smaller and can also make lower the ambient concentration. On the other hand, when the use of high-sink trees, the ambient concentration of this gas will increase again and the urban forest area that needed will be larger.